(untitled) (Marketing Journal, 2025)
The article provides a theoretical and practical analysis of the economic essence of regional development and the spatial distribution of industrial enterprises. Regional development is viewed as a strategic factor in the rational allocation of productive forces within the economic system, the efficient use of resources, and the reduction of economic disparities between regions. In this context, the location of industrial enterprises serves as a key driver of regional economies, ensuring the optimization of production capacities, the effective mobilization of labor resources, and infrastructure synergy. The study systematically examines the main factors revealing the economic essence of industrial placement — resource allocation, transport and logistics syst ems, labor market dynamics, investment activity, and scientific -technical potential. Furthermore, based on international experience, the article highlights modern approaches to industrial location, their integration into regional development strategies, and their impact on economic efficiency. The research findings are aimed at developing theoretical and practical recommendations for diversifying Uzbekistanʼs regional economy, ensuring territorially balanced industrial placement, and strengthening economic stability.